1998
DOI: 10.1165/ajrcmb.18.1.2878
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Type II and Clara Cells for Adenovirus-mediated Gene Transfer Using the Surfactant Protein B Promoter

Abstract: We examined the ability of the human surfactant protein B (SP-B) promoter to confer cell specificity of transgene expression in an adenoviral vector. Using similar replication-deficient adenoviruses (rAd), we compared lacZ reporter gene expression driven by the human SP-B promoter (rAd.SPBlacZ) with the ubiquitously expressed Rous sarcoma virus promoter (rAd.RSVlacZ). rAd.SPBlacZ expressed lacZ in H-441 and A549 lung epithelial cell lines and not in HeLa cells whereas rAd.RSVlacZ expressed in all three cell li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
1

Year Published

1999
1999
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(17 citation statements)
references
References 51 publications
0
16
0
1
Order By: Relevance
“…Surfactant protein B (SP-B) expression is also limited to lung cells (20)(21)(22)(23). Strayer et al (24) showed that an adenoviral vector that expresses the lacZ gene driven by the 5' flanking region of the SP-B promoter (rAd.SPB.lacZ) targeted H441 and A549 adenocarcinoma cells but not HeLa cervical cancer cells and primary human fetal lung fibroblasts. In contrast, an adenoviral vector that expresses the lacZ gene driven by the constitutive RSV promoter (rAd.RSV.lacZ) targeted all the cells tested.…”
Section: Tissue-specific Promoter Systemsmentioning
confidence: 99%
“…Surfactant protein B (SP-B) expression is also limited to lung cells (20)(21)(22)(23). Strayer et al (24) showed that an adenoviral vector that expresses the lacZ gene driven by the 5' flanking region of the SP-B promoter (rAd.SPB.lacZ) targeted H441 and A549 adenocarcinoma cells but not HeLa cervical cancer cells and primary human fetal lung fibroblasts. In contrast, an adenoviral vector that expresses the lacZ gene driven by the constitutive RSV promoter (rAd.RSV.lacZ) targeted all the cells tested.…”
Section: Tissue-specific Promoter Systemsmentioning
confidence: 99%
“…In part, this situation reflects the importance of SP-B protein in surfactant physiology (Curstedt et al, 1987;Nogee et al, 1993). However, analysis of SP-B transcription has been greatly facilitated by the use of a human Clara cell tumor line, H441, which expresses SP-B (Bohinski et al, 1994;Bingle, 1997;Strayer et al, 1998). These studies have shed considerable light on the activation of SP-B transcription.…”
Section: Discussionmentioning
confidence: 99%
“…Gene therapy has been widely investigated in cell-selective targeting. 184 Alveolar macrophages are an attractive vehicle by which to deliver a chemotherapeutic agent to the lymph nodes through the lymphatic circulation. Liposomes and microspheres are generally engulfed by alveolar macrophages.…”
Section: Cell Targetingmentioning
confidence: 99%